2013
DOI: 10.1123/ijspp.8.5.517
|View full text |Cite
|
Sign up to set email alerts
|

Training and Competition Workloads and Fatigue Responses of Elite Junior Cricket Players

Abstract: Purpose:This study investigated key fatigue and workload variables of cricket fast bowlers and nonfast bowlers during a 7-wk physical-preparation period and 10-d intensified competition period.Methods:Twenty-six elite junior cricketers (mean ± SD age 17.7 ± 1.1 y) were classified as fast bowlers (n = 9) or nonfast bowlers (n = 17). Individual workloads were measured via global positioning system technology, and neuromuscular function (countermovement jump [relative power and flight time]), endocrine (salivary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 25 publications
3
39
0
Order By: Relevance
“…This could be the reason why no differences were found between the high-intensity movements in the training and the ODG. These findings are in line with those reported in previous research [17] showing that fast bowlers consistently performed at greater intensities than the other sub-disciplines.…”
Section: Discussionsupporting
confidence: 93%
“…This could be the reason why no differences were found between the high-intensity movements in the training and the ODG. These findings are in line with those reported in previous research [17] showing that fast bowlers consistently performed at greater intensities than the other sub-disciplines.…”
Section: Discussionsupporting
confidence: 93%
“…The discrepant reports may be related to methodological differences between studies, with inconsistencies in the time taken between exercise cessation and testing, changes in the load placed on the individual and, importantly, differences in the modes of exercise under investigation. Of interest, the insensitivity of jump height to training and matches in our study supports the only other paper investigating neuromuscular fatigue in cricket 4 .…”
Section: Discussionsupporting
confidence: 85%
“…Research in cricket has typically reported external measures of workload (i.e. training doses) from global positioning system (GPS) tracking 1 , time motion analysis (TMA) 2 , number of overs bowled [3][4][5] whilst internal loads have been quantified using subjective measures, such as perception of effort 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with the irruption of new more accessible technology and software, the use of methods to control and quantify the TL have been spread in different sports [3][4][5]. Furthermore, beyond the improvement of performance perspective, the quantification of the TL can prevent from suffering non-functional overreaching, injuries or illnesses avoiding workload spikes [6][7][8].…”
Section: Opinionmentioning
confidence: 99%